Cultural violence against women in Thai films: perspective from multi-sector stakeholders - Napat Ruangnapakul; Norhafezah Yusof; Norsiah Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2018)
There are many forms of violence in films regarding culturally unique factors that are expected to influence attitudes towards violence against women. The purpose of this study is to examine cultural violence against women in three films directed by a prominent Thai film director, Bhandevanov Devakula: The Eternity, The Outrage, and Jan Dara. A series of in-depth interviews with informants who are the stakeholders at the civil society level was conducted in Thailand. The informants were three policymakers, five academics, three non-governmental organisation (NGO) leaders, two film critics, two film directors, and a newspaper editor in Thailand. The data were analysed thematically using NVivo 10 software. The results of this study indicated that the informants identified cultural violence in the form of marriage bondage, power acceptance, cynical attitude, keeping women in customary roles, self-control, and gender bias. The cultural violence was depicted in the form of direct violence. This study also found that the stakeholders from diverse backgrounds noticed and framed the meaning of cultural violence in different ways. The significance of this study is in providing a deep understanding of the circumstances associated with cultural violence against women in Thai films that reflect the Thai context from the perspectives of stakeholders from multiple sectors. This study benefits the film industry and film classification by drawing attention to the cultural violence against women in films and thereafter minimizing it. The future researchers may extend examining cultural violence against women in terms of indirect and direct violence in Asian based films.